The Gut Microbiota as an Influencing Factor of Arterial Thrombosis - Reinhardt, Christoph (Hämostaseologie, 2019)
The mutualistic gut microbiota does not only impact the development and function of various immune cell types, but it also influences the function of the hepatic vascular endothelium and prothrombotic platelet function. With germ-free mouse models, we have demonstrated that gut-derived microbial-associated molecular patterns could stimulate hepatic von Willebrand factor (VWF) synthesis and plasmatic VWF levels through Toll-like receptor-2 (TLR2), thus defining the extent of platelet deposition to the subendothelial matrix of the ligation-injured common carotid artery. In addition to the microbiota-derived choline metabolite trimethylamine N-oxide and the microbiota's regulatory role on the colonic serotonin biosynthesis pathway, affecting prothrombotic platelet function, TLR2-regulated hepatic endothelial VWF synthesis and elevated VWF plasma levels constitute a pivotal mechanism of how the gut microbiota is linked to arterial thrombosis. Conceptually, in addition to the identified functions of the gut microbiota in modulating host nutrition and metabolism, our work places the innate immune functions of the liver sinusoidal endothelium as an actuating variable in arterial thrombus growth.
Keywords: microbiota; germ-free; coagulation; thrombosis